Bacteriological examination of children diagnosed of meningitis in Lagos, Nigeria - Moro, Dauphin Dighitoghi (International Journal of Scientific Research in Biological Sciences, 2021)
Bacterial meningitis results from an inflammation of the meninges of the brain by bacteria and bacterial products which is characterized by high prevalence in neonates and children. Patients at risk for bacterial meningitis include newborns, people in developing countries and those already infected with Gram-negative bacilli. This study was carried out to isolate, identify and characterize bacterial pathogens associated with cerebrospinal meningitis in children as well assess their antibiotic resistant patterns. A total of 318 samples were collected for bacteriological analysis at the children emergency wards of two hospitals for 24 months. All children diagnosed of meningitis were enrolled after obtaining informed consent from their parents. Aliquots of cerebrospinal fluids were collected by attending physician after lumbar puncture. Microscopy and culture, CSF protein and CSF glucose analyses were done. Of 318 samples analyzed, eighty two Gram stains indicated the presence of bacterial cells, 36 only of which had positive culture. Relationship between glucose and protein levels with Gram staining of CSF was observed. Bacteria were identified with standard microbiological methods included: Streptococcus species (12), Staphylococci (8), Acinetobacter iwoffi (6), Escherichia coli (4), Klebsiella pneumoniae (4) and Serratia rubidala (2). Most previously dominant organisms in bacterial meningitis were not isolated. Male patients were more predisposed to bacterial invasion with a higher number of cases in those less than one year. The routine use of polymerase chain reaction (PCR) and nucleic acid probes will surely provide rapid and definitive diagnosis of meningitis.